Back Cover: Reversible Pore Size Control of Elastic Microporous Material by Mechanical Force (Chem. Eur. J. 39/2013). Issue 39 (19th September 2013) - Ito, Masashi; Nishihara, Hirotomo; Yamamoto, Kentaro; Itoi, Hiroyuki; Tanaka, Hideki; Maki, Akira; Miyahara, Minoru T.; Yang, Seung Jae; Park, Chong Rae; Kyotani, Takashi
<x xml:space="preserve">Abstract</x> Zeolite‐templated carbon is extraordinarily flexible and behaves as a kind of elastic microporous material, unlike other microporous materials, such as activated carbons, zeolites, and metal–organic frameworks. Its uniform micropores (1.2 nm) can be contracted/recovered reversibly just by loading mechanical force, and such pore‐size change induces noticeable increase in gas‐physisorption amount. For more details see the Full Paper by H. Nishihara et al. on page 13009 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>